Cerebellar networks in individuals at ultra high‐risk of psychosis: Impact on postural sway and symptom severity. Issue 8 (24th January 2014) - Bernard, Jessica A.; Dean, Derek J.; Kent, Jerillyn S.; Orr, Joseph M.; Pelletier‐Baldelli, Andrea; Lunsford‐Avery, Jessica R.; Gupta, Tina; Mittal, Vijay A.
Abstract: Despite known deficits in postural control in patients with schizophrenia, this domain has not been investigated in youth at ultra high‐risk (UHR) for psychosis. This is particularly relevant as postural control implicates dysfunction in the cerebellum‐a region implicated in cognitive dysmetria conceptions of schizophrenia but poorly understood in the prodrome. Here, we extended our understanding of movement abnormalities in UHR individuals to include postural control, and have linked these deficits to both symptom severity and cerebello‐cortical network connectivity. UHR and healthy control participants completed an instrumentally based balance task to quantify postural control along with a resting state brain imaging scan to investigate cerebellar networks. We also quantified positive and negative symptom severity with structured clinical interviews. The UHR group showed overall increased postural sway and decreased cerebello‐cortical resting state connectivity, relative to controls. The decreased cerebello‐cortical connectivity was seen across multiple networks. Postural sway was also correlated with cerebellar connectivity in this population and uniquely positively correlated with the severity of negative symptoms. Finally, symptom severity was also associated with cerebellar connectivity. Together, our results point to a potential deficit in sensory integration as an underlying contributor to the increased postural sway, and provide evidence of cerebellar abnormalities in UHR individuals. These results extend our understanding of the motor abnormalities of UHR individuals beyond striatum‐based dyskinesias to include postural control and sensory integration deficits, and implicate the cerebellum as a distinct neural substrate preceding the onset of psychosis. Taken together, our results extend the cognitive dysmetria framework to UHR populations. Hum Brain Mapp 35:4064–4078, 2014 . © 2014 Wiley Periodicals, Inc .